Políticas de permanência estudantil em cursos de licenciaturas no período de 2007 a 2017: a experiência da Universidade Federal do Triângulo Mineiro - Campos, Liliane Carla (2018)
In this study, centrally, we investigate and analyze student permanence policies and university evasion prevention actions adopted by the teacher training courses of the Federal University of the Triângulo Mineiro. Specifically, we seek to situate the policies and actions of promotion of student permanence and of prevention of university evasion at the UFTM, in the context of the recent educational policies of expansion higher education. In addition, we reflect on the phenomenon of university evasion in undergraduate courses, at the national level and specifically at the UFTM, and also identify and analyze the determinants of avoidance in the context of university teacher training courses. We develop an investigation of a qualitative nature, with analyzes based on dialectical historical materialism, since such this epistemological perspective allows the understanding and transformation of reality through the analysis of historical and social contradictions that permeate society, in a critical perspective. As methodological procedures, we adopted a documental and bibliographic review, and questionnaire application to the coordinators of the UFTM teacher training courses and to the managers related to the areas of planning, teaching and student assistance. In the theoretical framework, we use the contributions of Azevedo (1997), Pereira (2008), Sguissardi (2003, 2004, 2009, 2015), Cordiolli (2011), Shiroma, Moraes and Evangelista (2002), Trópia (2009), Dourado (2002), Saviani (2007), Gentili and Oliveira (2013), Gatti (2010), Gatti and Barreto (2009), Ristoff (2008), Nascimento (2013; 2017), Mancebo (2017), among others. We verify that the actions of the university are in tune with the National Policy of Student Assistance (PNAES). However, we have identified that UFTM's teacher training courses do not have specific programs and actions to strengthen student stay and prevent university dropouts. In addition, we identified that the main agents that stimulate evasion in such courses, from the perspective of students, are: difficulty in reconciling work and studies; financial difficulties; teachers didactics; among others. For the coordinators of the teacher training courses, the causes of student abandonment are, in turn: difficulty in reconciling work and studies; personal problems (health, family, love relationships); deficient training in basic education (difficulties in writing, reading and interpreting texts); devaluation of the teaching profession, preference for other undergraduate courses and infrastructure of the institution. Finally, for managers in the areas of planning, teaching and student assistance, the causes of dropout are related to teachers didactics, followed by financial difficulties, devaluation of the teaching profession, difficulty in reconciling work and studies, institutional infrastructure, personal problems, pedagogical projects of the courses, among others. We emphasize that, in this study, we start from the concrete reality, we reflect on the current educational policies of higher education, considering the current context of mercantilization of educational processes. We demonstrated that student permanence in UFTM teacher training courses lacks specific actions and programs that minimize university evasion and guarantee the real democratization of this level of education.